The effect of cash, vouchers, and food transfers on intimate partner violence: Evidence from a randomized experiment in northern Ecuador - Hidrobo, Melissa; Peterman, Amber; Heise, Lori (American Economic Association, 2016)
Using a randomized experiment in Ecuador, this study provides evidence on whether cash, vouchers, and food transfers targeted to women and intended to reduce poverty and food insecurity also affected intimate partner violence. Results indicate that transfers reduce controlling behaviors and physical and/or sexual violence by 6 to 7 percentage points. Impacts do not vary by transfer modality, which provides evidence that transfers not only have the potential to decrease violence in the short-term, but also that cash is just as effective as in-kind transfers. (JEL I38, J16, K42, O15, O17)